La motricidad fina para mejorar el proceso de escritura de los niños de educación inicial II sección vespertina de la escuela de educación básica Miguel Riofrío de la ciudad de Loja, periodo 2017-2018 - Jumbo Quezada, María Belén (2018)
The present investigative work entitled: THE FINE MOTORCYCLE TO IMPROVE THE WRITING PROCESS OF CHILDREN OF INITIAL EDUCATION II SECTION VESPERTINA OF THE SCHOOL OF BASIC EDUCATION MIGUEL RIOFRÍO OF THE CITY OF LOJA, PERIOD 2017-2018. The general objective was to determine the incidence of fine motor skills in the writing process of children in Initial Education II. The type of research is experimental, and the methods used were scientific, analyticalsynthetic, deductive, inductive, and statistical; To obtain the information, the observation, the survey directed to the teacher, the application of the "Gooddard Dexterímetro" test and the application of the checklist of the writing process to 12 children investigated, the data obtained in the pre -test and post-test were entered in the statistical software PSS23, in the results obtained after the application of the didactic guide, an arithmetic mean of 3 was obtained in the fine motor skills; while in the writing process an arithmetic mean of 2.3333 was obtained; evidencing a significant increase. This allows us to conclude that the application of the didactic guide and the development of it during all the days of classes helps to improve the fine motor skills and therefore the writing process of the children of Initial Education II. It is recommended that teachers use activities based on graphoplastic techniques as a resource for the daily development of their classes, in order to achieve the various benefits that are achieved with these activities in the development of their children